2010
DOI: 10.1177/0010414010369072
|View full text |Cite
|
Sign up to set email alerts
|

Corruption and Trust: Theoretical Considerations and Evidence From Mexico

Abstract: The growing empirical literature on political corruption shows trust (interpersonal and political) to be both cause and consequence of corruption: a conclusion that largely builds on studies using cross-national measures of corruption based on perceptions of corruption rather than actual experience, raising questions of endogeneity. The lack of trust fed by corruption is considered critical in that it undermines government efforts to mobilize society to help fight corruption and leads the public to routinely d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
216
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(240 citation statements)
references
References 48 publications
16
216
0
8
Order By: Relevance
“…Whether or not public servants engage in corrupt behavior alters the amount of state resources available for public service delivery, as well as the trust citizens place in government (see, e.g., Morris & Klesner, 2010;S. Rose-Ackerman, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Whether or not public servants engage in corrupt behavior alters the amount of state resources available for public service delivery, as well as the trust citizens place in government (see, e.g., Morris & Klesner, 2010;S. Rose-Ackerman, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Rabl & Kuhlmann (2009) noted that rationalisation may possess potential determinant of corrupt behaviour. In yet another study, trust was found to have a mutual causality with corruption (Morris & Klesner, 2010). Personal characteristics such as gender, marital status, education, labour, religion, and perception on democratic state of a nation have also been found to influence individual's perception on corruption (Melgar, Rossi, & Smith, Perceptions of Corruption in a Cross-Country Perspective: Why are Some Individuals More Corruption Than Others?, 2010).…”
Section: Literature Reviewmentioning
confidence: 98%
“…It is also correlated with a reduction in belief that democracy is effective (Anderson and Tverdova 2003). Experiences of corruption have also been shown to reduce trust in government officials (Seligson 2002;Anderson and Tverdova 2003;Eek and Rothstein 2009;Morris and Klesner 2010). These effects may be strongest among the poor (Manzetti and Wilson 2007).…”
Section: Policy Relevancementioning
confidence: 99%